The Disrespectfulness of Weighted Survival Lotteries. Issue 3 (7th April 2021) - Adams, Joseph
Abstract: If we can save the lives of only one of multiple groups of people, we might be inclined simply to save whichever group is largest. We may worry, though, that automatically saving the largest group fails to take each saveable individual sufficiently into account, offering some of these individuals no chance at all of being rescued. Still wanting to give larger groups higher chances of survival, we may then say that we ought to employ a proportionally weighted lottery to determine which group to save. In this paper, I argue that this would be a mistake. Given the most plausible way of specifying it, the weighted-lottery view itself fails to treat each saveable individual with equal moral respect.